Pengembangan Modul Pembelajaran Ekonomi Berbasis Guided Inquiry Untuk Meningkatkan Hasil Belajar Siswa Kelas Xi MA NW Sukamulia Tahun Pelajaran 2017/2018 - Sholihah, Isfi; Fahrurrozi, Muh (Universitas Hamzanwadi, 2017)
This study aims to: 1) analyze the development of guided inquiry-based economic learning module to improve student learning outcomes of grade XI MA NW Sukamulia; 2) to analyze the effectiveness of the use of guided inquiry-based economic learning module to improve student learning result of class XI MA NW Sukamulia.The study of the development of this economic learning module using the modified Borg and Gall procedure consists of 8 stages: 1) preliminary research and information gathering, 2) planning, 3) development of initial product form, 4) limited testing, 5) revision of the main product , 6) extensive test, 7) revision of operational product, 8) field test. Data analysis used during development is descriptive analysis, module feasibility analysis based on criteria score, and analysis of student learning result using t-test.Based on the results of descriptive analysis of economic learning modules based on guided inquiry concluded that the validation of design experts / views as much as 4.6% with good criteria, material experts as much as 3.7% with good criteria. After obtained the validation results can then be done field trials. Based on the results of the experiment, there were 35 complete students and 5 unfinished students with an average score of 81.2% and 87.5% classical percentage. Judging from the results of learning, the use of teaching materials is also an impact on student learning outcomes. This shows that the economic learning module as a result of development can help facilitate the students in learning. Result of questionnaire of student requirement analysis, from 40 respondents obtained total 320 for